Efektivitas Socio Dramatic Play untuk Meningkatkan Kemandirian pada Anak Usia Prasekolah - Nadya Comanechie E L (PG-PAUD Trunojoyo, 2014)
Independence is an important stage in a child‟s development task and need trained, so it will be individuals who are independence to teenagers and even into adulthood later. The purpose of this study was to determine the effectiveness of socio-dramatic play to increase the independence of pre-school age children. The method used in this study was a quasi experimental, with the design of the study one group pretest-posttest. Subjects were 10 children of preschool age. Interrater reliability using the reliability, by calculating the observation of tree-observer agreement. From the calculation of the level of reliability of the measuring instrument used is obtained from the three observers more than 50%,which means that the reliability of observation quite reliable pass judgment on those aspects of independence. Test the validity of the used content validity were obtained by professional judgment. Data were analyzed using Wilcoxon signed rank test to determine differences before and after a given treatment.Recording the measurement result using rating pretest and posttest was found there are significant differences in the preschool child‟s independence. Significance value obtained after the Wilcoxon signed rank test calculations are (2-tailed) 0,005 0,05. So it can be concluded that the socio-dramatic play effective in increasing independence in preschoolers.